Analysis Of Queueing System And Teller’s Serviceoptimization At The Sub-Branch Office Of Bank Bjb For The Regional Government Of West Bandung Regency - Muhamad Reza Kamil Risnaedi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study investigates the queuing system and service efficiency at the Bank BJB sub-branch office in West Bandung Regency, focusing on enhancing customer service operations. With the significant increase in banking sector customers in Indonesia, including a growth in accounts in both conventional and digital financial institutions, the banking industry faces challenges in maintaining speed and efficiency in customer service. Long queues and time-consuming services have led to customer dissatisfaction and reduced operational efficiency​​.The research examines the current performance of the queuing system and teller service time, analyzing the root causes of prolonged waiting and service times, and developing strategies to optimize these times​​. The Bank BJB KCP serves a varied customer base, with complex banking requirements that often lead to longer service times​​. The queuing system employs a multi-channel, single-phase model, and the tellers offer several services, each with its own service level agreement​​.Observational data collected over 12 working days revealed the busiest hours and performance metrics, indicating high congestion during peak hours​​. Root cause analysis, considering both teller and customer perspectives, identified key issues contributing to the queuing system's inefficiency. The study's findings aim to enhance the overall customer service efficiency at Bank BJB KCP.